Generation Y’s political participation and social media in Malaysia - Norshuhada Shiratuddin,; Mohd Azizuddin Mohd Sani,; Shahizan Hassan,; Mohd Khairie Ahmad,; Kartini Aboo Talib @ Khalid,; Noor Sulastry Yurni Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper attempts to study the role of Generation Y in expressing their problems, engaging the government through the media especially the social media, and in deciding and voicing their views in the ballot box during the 2008 and 2013 general elections. Generation Y has utilized the social media after the traditional media, like the print and broadcasting media, give them limited space for them to engage with the government and the oppositions Therefore, a survey had been conducted in studying the perception of Generation Y towards media and political participation. This research was able to gather 1,029 respondents from the age 15 till 25 years old. In overall, the findings show that this generation was a little bit sceptical on the new media but they believe that the new media can be the best tool for the youth to engage more with the government. Therefore, it is clear that the result of the survey election is in line with the importance of social media and Generation Y in dominating the public sphere in Malaysia.